1998
DOI: 10.3354/meps170025
|View full text |Cite
|
Sign up to set email alerts
|

A close relationship between algicidal bacteria and termination of Heterosigma akashiwo (Raphidophyceae) blooms in Hiroshima Bay, Japan

Abstract: ABSTRACT. Blooms of the noxious red tide phytoplankton Heterosigma akashiwo (Raphidophyceae) occurred in Hiroshima Bay. Japan. in 1994 and 1995. During these blooms we monitored rnicroorganisms which killed H. akashiwo by use of the microplate MPN (most probable number) method using an axenic culture of H. akashiwo as a susceptible host organism. At every sampling site abundance of algicidal microorganisms in seawater samples filtered through 0 8 pm nuclepore filters increased rapidly during the termination pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 20 publications
(41 reference statements)
1
43
0
1
Order By: Relevance
“…In 1995, the HAKB members of 2B, 2C and 2D accounted for 52 strains and corresponded to 89.7 % of all 1 6 s rDNA RFLPs analyzed (data not shown). The HAKB strains of ribotype 2C and 2D were especially dominant in the HAKB populations isolated a t Stn V on June 30 (19 strains of 2C and 8 strains of 2D were observed in 29 strains of HAKB), when the MPN of HAKB dramatically increased and was followed by disintegration of the Heterosigma akashiwo bloom (Kim et al 1998).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 1995, the HAKB members of 2B, 2C and 2D accounted for 52 strains and corresponded to 89.7 % of all 1 6 s rDNA RFLPs analyzed (data not shown). The HAKB strains of ribotype 2C and 2D were especially dominant in the HAKB populations isolated a t Stn V on June 30 (19 strains of 2C and 8 strains of 2D were observed in 29 strains of HAKB), when the MPN of HAKB dramatically increased and was followed by disintegration of the Heterosigma akashiwo bloom (Kim et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…These results strongly support the fact that the ribotyping by the 5 endonucleases used in this study was sufficiently powerful to resolve the population structure and dynamics of the HAKB. At Stn V in Hiroshima Bay in 1994 and 1995, Heterosigma akashiwo blooms occurred at the beginning of June and at the end of June, respectively (Kim et al 1998). In the both cases, the bloom at the surface dramatically disintegrated within a few days after the climax.…”
Section: Gy27 (2c) Gy21 (2b)mentioning
confidence: 99%
See 2 more Smart Citations
“…If red-tide algae ingest bacteria in a significantly large number, they may compete with HNFs and ciliates for bacterial prey, and the grazing impact by the algae on bacteria may make a considerable contribution to the total grazing impact of protistan predators on bacteria. However, there have been few studies on the feeding of red-tide algae on marine bacteria (Nygaard & Tobiesen 1993, Jeong et al 2005a, although there have been many studies on the interactions between red-tide algae and algicidal bacteria (Kim et al 1998, Doucette et al 1999, Imai et al 2001, Skerratt et al 2002, Mayali & Azam 2003. Nygaard & Tobiesen (1993) reported that some prymnesiophyte species, the raphidophyte Heterosigma akashiwo and the dinoflagellates Karlodinium micrum (previously Gyrodinium galatheanum) and Alexandrium tamarense were able to ingest bacteria, but H. akashiwo and K. micrum did not ingest bacteria when the phosphate concentrations were high (batch cultures, 0.33 to 1.56 µM).…”
Section: Introductionmentioning
confidence: 99%